Er-Yb co-doped high-P quartz glass and preparation method thereof

By using specific process steps to the proportion of front-drive body raw materials in the preparation of high phosphorus glass in ER-YB, the MCVD method is solved by the muddy unevenness and the unstable temperature control in the preparation of large-scale and high-concentration doping fiber preparation. The problem realizes the efficient pump conversion and the stability of the laser system.

CN119371098APending Publication Date: 2025-01-28POLYCORE PHOTONICS TECHNOLOGY (TAIZHOU) CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411942652.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

When preparing large-mode field, high-concentration Er-Yb co-doped high-phosphorus quartz glass fiber, the MCVD method has problems such as uneven doping and unstable temperature control, resulting in poor fiber performance.

Method used

A kind of ER-YB is mixed with high P quartz glass and its preparation method. It uses specific front-drive raw material ratio and process steps, including the formation of silicon oxide transparent solid solution, adding porous silica powder, ball grinding and vacuum melting For the steps, accurately control the distribution and doping ratio of the P element.

Benefits of technology

Realize the high doping and accurate distribution of the P element, solve the problem of uneven doping and unstable temperature control in traditional crafts, and prepare ER- YB is mixed with high P quartz glass, which improves the pump conversion efficiency of optical fiber and the stability of the laser system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371098A_ABST
    Figure CN119371098A_ABST
Patent Text Reader

Abstract

According to the Er-Yb co-doped high-P quartz glass and the preparation method thereof provided by the invention, high doping of the P element is realized and the distribution of the P element is accurately controlled through the preparation method, so that the problems that the Er-Yb co-doped quartz glass is difficult in high doping of P2O5, easy in phase separation and crystallization and easy in clustering of high-concentration Er ions are solved; the problems of uneven doping, unstable temperature control and the like in a traditional MCVD process are solved, the Er-Yb co-doped high-P quartz glass which is large in size, high in doping concentration, high in doping uniformity and low in loss can be prepared, and the Er-Yb co-doped large-mode-field optical fiber core rod is widely suitable for high-repetition-frequency solid-state laser gain materials and Er-Yb co-doped large-mode-field optical fiber core rods. Meanwhile, the method can significantly improve the pumping conversion efficiency of the Er-Yb co-doped optical fiber, and effectively reduce the nonlinear effect in the optical fiber, thereby improving the stability and long-term reliability of a laser system during high-power work.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rare earth doped quartz glass and optical fiber, and in particular to Er-Yb co-doped high-P quartz glass and a preparation method thereof. Background Art

[0002] Compared with traditional space microwave communication, space laser communication has obvious advantages in bandwidth capacity, weight, volume, etc., and is not restricted by the electromagnetic spectrum.

[0003] In my country's space laser communication systems, fiber laser amplifiers in the 1.5μm band are often used, in which Er-doped fibers and Er-Yb co-doped fibers are the main gain media. Traditionally, these fibers use 980nm laser diodes as pump sources. However, the absorption cross section of Er ions at 980nm is low, resulting in limited pump light absorption efficiency, which in turn affects the performance of Er-doped fibers. Although longer fibers can increase the absorption of pump light, the increase in fiber length can also induce nonlinear effects, especially at high powers, which limits the effectiveness of laser amplifiers. In addition, the agglomeration effect of Er ions in the quartz matrix also poses a challenge to the optimization of Er-doped fibers. In contrast, Er-Yb co-doped fibers are ideal for achieving 1.5μm high-power laser output due to their high gain, large absorption cross section, and high energy conversion efficiency. However, Er-Yb co-doped fiber in quartz matrix easily generates spontaneous radiation with a wavelength of 1μm, which significantly reduces the pump conversion efficiency of 1.5μm laser. At the same time, the quartz matrix has a low solubility for rare earth ions, which limits the sensitization efficiency of Yb ions to Er ions, thereby restricting the improvement of laser power. Studies have shown that the introduction of high-P components in quartz glass to form high-P quartz glass can significantly improve the solubility of rare earth ions and enhance the maximum phonon energy of the glass matrix. This improvement helps to optimize the doping ratio of Yb ions to Er ions, reduce the number of excited Yb ions, improve the energy transfer efficiency, fundamentally suppress the spontaneous radiation of Yb ions, and reduce the reverse energy transfer from Er ions to Yb ions, ultimately improving the pump conversion efficiency of Er-Yb co-doped fiber.

[0004] For rare earth doped fiber lasers, the fiber core is the core part that determines the performance of the fiber laser. Therefore, the preparation of the fiber core preform has always been the most important technology for fiber lasers. Especially for Er-Yb co-doped high-phosphorus quartz glass, SiO2 and P2O5 are two different glass formers, which are difficult to effectively fuse during the vitrification process, often leading to glass crystallization and even devitrification. 5+ Irregularities in ion volatilization can also lead to increased optical losses and depressions in the center of the fiber core refractive index, which can significantly affect the performance of the final product.

[0005] In order to solve these problems, most commercial doped optical fibers currently use a modified chemical vapor deposition (MCVD) method combined with solution doping technology to produce optical fiber preforms. The MCVD method has significant advantages in the preparation of traditional doped optical fiber preforms, and can achieve a more uniform doping distribution and higher preform quality. However, when preparing large mode field, high concentration doped optical fiber preforms, the MCVD method faces a series of challenges, especially in the production of optical fiber preforms with large core diameters, high doping concentrations and uniformity requirements, often resulting in problems such as low doping concentration, uneven refractive index distribution, and large volatility. Therefore, in order to meet the specific requirements of Er-Yb co-doped high-phosphorus silica optical fibers, a new non-CVD core glass preparation technology urgently needs to be broken through to achieve better size control, high concentration uniformity and overall performance improvement. Summary of the invention

[0006] In view of the problem that the MCVD method has certain limitations in the preparation of large mode field and high doping concentration optical fibers, especially in the uniform doping of high concentration P elements, the present invention provides an Er-Yb co-doped high P quartz glass and a preparation method thereof.

[0007] The Er-Yb co-doped high-P quartz glass of the present invention has the following molar percentages of components: Er2O3: 0.01mol% to 0.2mol%, Yb2O3: 0.05 to 1mol%, Al2O3: 0 to 3mol%, P2O5: 5mol% to 15mol%, and the remaining components are SiO2.

[0008] Another aspect of the present invention is a method for preparing Er-Yb co-doped high-P quartz glass, comprising the following steps: S1. Weigh the precursor raw materials of each component according to the selected molar percentage, the precursor raw material of Er2O3 is erbium chloride hexahydrate, the precursor raw material of Yb2O3 is ytterbium chloride hexahydrate, the precursor raw material of Al2O3 is aluminum chloride hexahydrate, the precursor raw material of P2O5 is phosphoric acid, 90wt% to 95wt% of the precursor raw material of SiO2 is porous silica powder, and 5wt% to 10wt% of the precursor raw material of SiO2 is derived from silicon alkoxide; S2. A mixed solution is prepared according to a volume ratio of silicon alkoxide: water: organic solvent = 1:2~10:4~20, and then erbium chloride hexahydrate, ytterbium chloride hexahydrate, aluminum chloride hexahydrate, and phosphoric acid are sequentially added to the mixed solution, and then a silicon alkoxide hydrolysis catalyst is added to adjust the pH value of the solution to a first pH value, and the mixture is stirred for 1 to 20 hours at room temperature to obtain Er 3+ , Yb 3+ , P 5+ Triple doping or Er 3+ , Yb 3+ 、Al 3+ , P 5+The silicon oxide transparent sol solution is added and allowed to stand for 1 to 5 days; S3. The porous silica powder is added in batches in a fixed amount to the vigorously stirred transparent silica sol solution, and stirring is continued for 2 to 48 hours after the addition is completed to form a suspension; S4. The suspension is granulated to obtain a preliminary powder, and then the preliminary powder is heated to 1000°C in an oxygen atmosphere in a tube furnace and kept at 1000°C for 5 to 20 hours to remove residual carbon and hydroxyl groups to form an Er-Yb co-doped high P silica powder; S5. The silica powder is ball-milled using a ball mill and the particle size is controlled to be below 100 μm; S6. The ball-milled silica powder is placed in a graphite crucible and placed in a high temperature furnace at 1500 to 1730°C for 10 -1 Up to 10 -3 The melting is carried out for 1 to 8 hours under a vacuum degree of torr, and bubble-free transparent glass is formed along with furnace cooling. The bubble-free transparent glass is Er-Yb co-doped high-P quartz glass.

[0009] Preferably, the molar percentage of each component content of Er-Yb co-doped high-P quartz glass is: Er2O3: 0.01mol% to 0.2mol%, Yb2O3: 0.05 to 1mol%, Al2O3: 0 to 3mol%, P2O5: 5mol% to 15mol%, and the remaining components are SiO2.

[0010] Preferably, the silicon alkoxide is Si(OC2H5)4 or Si(OCH3)4. When the silicon alkoxide is Si(OC2H5)4, the organic solvent is C2H5OH; when the silicon alkoxide is Si(OCH3)4, the organic solvent is CH3OH.

[0011] Preferably, the silicon alkoxide hydrolysis catalyst is hydrochloric acid or ammonia water. When the silicon alkoxide hydrolysis catalyst is hydrochloric acid, the first pH value is 1 to 3; when the silicon alkoxide hydrolysis catalyst is ammonia water, the first pH value is 8 to 10.

[0012] Preferably, the median particle size of the porous silica powder is in the micro-nano range.

[0013] Preferably, in step S3, the fixed addition amount is 1 to 5 g each time.

[0014] Preferably, in step S4, the suspension is granulated by rotary evaporation.

[0015] The method for preparing the Er-Yb co-doped high-P quartz optical fiber core rod according to the third aspect of the present invention comprises the following steps: The Er-Yb co-doped high-P quartz glass prepared by the above-mentioned preparation method of Er-Yb co-doped high-P quartz glass is subjected to cold working and polishing to obtain an optical fiber core rod, the surface roughness of the optical fiber core rod is less than 10nm, and the optical fiber core rod is placed in hydrofluoric acid with a mass concentration of 5 to 20% for acid treatment for 5 to 15 minutes, and then taken out and dried to obtain an Er-Yb co-doped high-P quartz optical fiber core rod.

[0016] The Er-Yb co-doped high-P quartz optical fiber core rod of the fourth aspect of the present invention is obtained by the above-mentioned preparation method of the Er-Yb co-doped high-P quartz optical fiber core rod.

[0017] Compared with the prior art, the Er-Yb co-doped high-P quartz glass and its preparation method of the present invention realize high doping of P element and accurately control the distribution of P element, solve the problems of Er-Yb co-doped quartz glass, such as difficulty in high doping of P2O5, easy phase separation and crystallization, and easy clustering of high-concentration Er ions, overcome the problems of uneven doping and unstable temperature control in the traditional MCVD process, and can prepare Er-Yb co-doped high-P quartz glass with large size, high doping concentration, high doping uniformity and low loss, which is widely applicable to high-repetition-rate solid-state laser gain materials and Er-Yb co-doped large-mode-field optical fiber core rods. At the same time, the method can significantly improve the pump conversion efficiency of Er-Yb co-doped optical fiber, and effectively reduce the nonlinear effect in the optical fiber, thereby improving the stability and long-term reliability of the laser system when working at high power. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0019] Figure 1 This is a physical picture of the Er-Yb co-doped high-P quartz optical fiber core rod made from Er-Yb co-doped high-P quartz glass in Example 1.

[0020] Figure 2 This is the EPMA surface scanning image of the Er-Yb co-doped high-P quartz glass in Example 2.

[0021] Figure 3 This is the EPMA line scan image of Er-Yb co-doped high-P quartz glass in Example 2.

[0022] Figure 4 Graph showing transmittance of Er-Yb co-doped high P quartz glass in the ultraviolet-visible band in Example 3.

[0023] Figure 5 Schematic diagram of the absorption spectrum (Ex = 980nm) of Er-Yb co-doped high-P quartz glass at room temperature in Example 3.

[0024] Figure 6 Schematic diagram of the emission spectrum (Ex = 980 nm) of Er-Yb co-doped high-P quartz glass at room temperature in Example 3. DETAILED DESCRIPTION

[0025] In order to provide a further understanding of the purpose, structure, features, and functions of the present invention, the following detailed description is given in conjunction with the embodiments.

[0026] In the description of the present invention, it should be noted that the terms "center", "up", "down", "left", "right", "vertical", "horizontal", "inside", "outside", etc. indicate directions or positional relationships based on the directions or positional relationships shown in the accompanying drawings. They are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction. Therefore, they cannot be understood as limitations on the present invention.

[0027] The Er-Yb co-doped high-P quartz glass of the present invention has the following molar percentages of components: Er2O3: 0.01mol% to 0.2mol%, Yb2O3: 0.05 to 1mol%, Al2O3: 0 to 3mol%, P2O5: 5mol% to 15mol%, and the remaining components are SiO2.

[0028] Another aspect of the present invention is a method for preparing Er-Yb co-doped high-P quartz glass, comprising the following steps: S1. Weigh the precursor raw materials of each component according to the selected molar percentage, the precursor raw material of Er2O3 is erbium chloride hexahydrate, the precursor raw material of Yb2O3 is ytterbium chloride hexahydrate, the precursor raw material of Al2O3 is aluminum chloride hexahydrate, the precursor raw material of P2O5 is phosphoric acid, 90wt% to 95wt% of the precursor raw material of SiO2 is porous silica powder, and 5wt% to 10wt% of the precursor raw material of SiO2 is derived from silicon alkoxide; S2. A mixed solution is prepared according to a volume ratio of silicon alkoxide: water: organic solvent = 1:2~10:4~20, and then erbium chloride hexahydrate, ytterbium chloride hexahydrate, aluminum chloride hexahydrate, and phosphoric acid are sequentially added to the mixed solution, and then a silicon alkoxide hydrolysis catalyst is added to adjust the pH value of the solution to a first pH value, and the mixture is stirred for 1 to 20 hours at room temperature to obtain Er 3+ , Yb 3+ , P 5+ Triple doping or Er 3+ , Yb 3+ 、Al3+ , P 5+ The silicon oxide transparent sol solution is added and allowed to stand for 1 to 5 days; S3. The porous silica powder is added in batches in a fixed amount to the vigorously stirred transparent silica sol solution, and stirring is continued for 2 to 48 hours after the addition is completed to form a suspension; S4. The suspension is granulated to obtain a preliminary powder, and then the preliminary powder is heated to 1000°C in an oxygen atmosphere in a tube furnace and kept at 1000°C for 5 to 20 hours to remove residual carbon and hydroxyl groups to form an Er-Yb co-doped high P silica powder; S5. The silica powder is ball-milled using a ball mill and the particle size is controlled to be below 100 μm; S6. The ball-milled silica powder is placed in a graphite crucible and placed in a high temperature furnace at 1500 to 1730°C for 10 -1 Up to 10 -3 The melting is carried out for 1 to 8 hours under a vacuum degree of torr, and bubble-free transparent glass is formed along with furnace cooling. The bubble-free transparent glass is Er-Yb co-doped high-P quartz glass.

[0029] Preferably, the molar percentages of the components of the Er-Yb co-doped high-P quartz glass are: Er2O3: 0.01mol% to 0.2mol%, Yb2O3: 0.05 to 1mol%, Al2O3: 0 to 3mol%, P2O5: 5mol% to 15mol%, and the remaining components are SiO2.

[0030] Preferably, the silicon alkoxide is Si(OC2H5)4 or Si(OCH3)4. When the silicon alkoxide is Si(OC2H5)4, the organic solvent is C2H5OH; when the silicon alkoxide is Si(OCH3)4, the organic solvent is CH3OH.

[0031] Preferably, the silicon alkoxide hydrolysis catalyst is hydrochloric acid or ammonia water. When the silicon alkoxide hydrolysis catalyst is hydrochloric acid, the first pH value is 1 to 3; when the silicon alkoxide hydrolysis catalyst is ammonia water, the first pH value is 8 to 10.

[0032] Preferably, in step S3, the fixed addition amount is 1 to 5 g each time.

[0033] Preferably, in step S4, the suspension is granulated by rotary evaporation.

[0034] The method for preparing the Er-Yb co-doped high-P quartz optical fiber core rod according to the third aspect of the present invention comprises the following steps: The Er-Yb co-doped high-P quartz glass prepared by the above-mentioned preparation method of Er-Yb co-doped high-P quartz glass is subjected to cold working and polishing to obtain an optical fiber core rod, the surface roughness of the optical fiber core rod is less than 10nm, and the optical fiber core rod is placed in hydrofluoric acid with a mass concentration of 5 to 20% for acid treatment for 5 to 15 minutes, and then taken out and dried to obtain an Er-Yb co-doped high-P quartz optical fiber core rod.

[0035] The Er-Yb co-doped high-P quartz optical fiber core rod of the fourth aspect of the present invention is obtained by the above-mentioned preparation method of the Er-Yb co-doped high-P quartz optical fiber core rod.

[0036] In actual use, porous silica refers to an amorphous silica powder with a certain porosity and a median particle size in the micro-nano range. The powder includes but is not limited to that prepared by vapor deposition.

[0037] Table 1: Specific components of Er-Yb co-doped high P quartz glass in 6 examples

[0038] Embodiment 1: The components of the Er-Yb co-doped high P quartz glass of this embodiment are: 0.05mol% Er2O3, 0.7mol% Yb2O3, 5mol% P2O5, 94.25mol% SiO2, and the preparation method thereof comprises the following steps: S1. Weighing the precursor raw materials of each component according to the selected molar percentage, the precursor raw material of Er2O3 is erbium chloride hexahydrate, the precursor raw material of Yb2O3 is ytterbium chloride hexahydrate, the precursor raw material of P2O5 is phosphoric acid, 90wt% of the precursor raw material of SiO2 is porous silica powder, and 10wt% of the precursor raw material of SiO2 is derived from silicon alkoxide; S2. Prepare a mixed solution in a volume ratio of silicon alkoxide: water: organic solvent = 1:6:12, wherein silicon alkoxide is Si(OC2H5)4 and organic solvent is C2H5OH. Add erbium chloride hexahydrate, ytterbium chloride hexahydrate and phosphoric acid to the mixed solution in sequence and stir well. Then, add silicon alkoxide hydrolysis catalyst HCl, adjust the pH value of the solution to a first pH value of 3, stir well at room temperature for 10 hours, and obtain Er 3+ , Yb 3+ , P 5+ The three-doped silicon oxide transparent sol solution was left to stand for another 3 days; S3. The porous silica powder was added in batches in a fixed amount of 3 g each time to the vigorously stirred transparent silica sol solution, and stirring was continued for 30 h after the addition to form a suspension; S4. Granulate the suspension by rotary evaporation to obtain a preliminary powder containing a certain amount of water and organic matter. Subsequently, place the preliminary powder in a tube furnace, slowly increase the temperature from 50°C to 1000°C at a rate of 1°C per minute in an oxygen atmosphere, and keep it at 1000°C for 10 hours to remove residual carbon and hydroxyl groups to form Er-Yb co-doped high-P silica powder; S5. ball milling the silica powder using a ball mill to control the particle size to be less than 100 μm; S6. The ball-milled silica powder was placed in a graphite crucible and heated in a high temperature furnace at 1730°C for 10 -3 The glass is melted for 4 hours under a vacuum degree of 0.1 torr and cooled in the furnace to form bubble-free transparent glass, which is Er-Yb co-doped high-P quartz glass.

[0039] The bubble-free transparent glass is cold processed and polished to obtain an optical fiber core rod, the surface roughness of the optical fiber core rod is less than 10nm, and the optical fiber core rod is placed in hydrofluoric acid with a mass concentration of 15% for acid treatment for 10 minutes, then taken out and dried to obtain an Er-Yb co-doped high-P quartz optical fiber core rod.

[0040] Figure 1 This is a physical picture of the Er-Yb co-doped high-P quartz optical fiber core rod made of Er-Yb co-doped high-P quartz glass in Example 1, whose size is ≥5×100 mm (5×100 mm means the core rod diameter is 5 mm and the core rod length is 100 mm), which fully meets the demand of large mode field optical fiber for large-size Er-Yb co-doped high-P quartz core rod.

[0041] Embodiment 2: The components of the Er-Yb co-doped high P quartz glass of this embodiment are: 0.05mol% Er2O3, 0.7mol% Yb2O3, 15mol% P2O5, 84.25mol% SiO2, and the preparation method thereof comprises the following steps: S1. Weighing the precursor raw materials of each component according to the selected molar percentage, the precursor raw material of Er2O3 is erbium chloride hexahydrate, the precursor raw material of Yb2O3 is ytterbium chloride hexahydrate, the precursor raw material of P2O5 is phosphoric acid, 90wt% of the precursor raw material of SiO2 is porous silica powder, and 10wt% of the precursor raw material of SiO2 is derived from silicon alkoxide; S2. Prepare a mixed solution in a volume ratio of silicon alkoxide: water: organic solvent = 1:6:12, wherein silicon alkoxide is Si(OC2H5)4 and organic solvent is C2H5OH. Add erbium chloride hexahydrate, ytterbium chloride hexahydrate and phosphoric acid to the mixed solution in sequence and stir well. Then, add silicon alkoxide hydrolysis catalyst HCl, adjust the pH value of the solution to a first pH value of 3, stir well at room temperature for 10 hours, and obtain Er 3+ , Yb3+ , P 5+ The three-doped silicon oxide transparent sol solution was left to stand for another 3 days; S3. The porous silica powder was added in batches in a fixed amount of 3 g each time to the vigorously stirred transparent silica sol solution, and stirring was continued for 30 h after the addition to form a suspension; S4. Granulate the suspension by rotary evaporation to obtain a preliminary powder containing a certain amount of water and organic matter. Subsequently, place the preliminary powder in a tube furnace, slowly increase the temperature from 50°C to 1000°C at a rate of 1°C per minute in an oxygen atmosphere, and keep it at 1000°C for 10 hours to remove residual carbon and hydroxyl groups to form Er-Yb co-doped high-P silica powder; S5. ball milling the silica powder using a ball mill to control the particle size to be less than 100 μm; S6. The ball-milled silica powder was placed in a graphite crucible and heated in a high temperature furnace at 1730°C for 10 -3 The glass is melted for 4 hours under a vacuum degree of 0.1 torr and cooled in the furnace to form bubble-free transparent glass, which is Er-Yb co-doped high-P quartz glass.

[0042] The bubble-free transparent glass was cold processed and polished into 2 mm thick Er-Yb co-doped high-P quartz sheet glass for optical and spectral performance testing and evaluation.

[0043] Figure 2 This is the EPMA surface scan of Er-Yb co-doped high-P quartz glass in Example 2. As can be seen from the figure, P, Yb, and Er elements are evenly distributed without obvious agglomeration or segregation, indicating that the material has achieved highly uniform doping on a microscopic scale. This uniformity fully meets the uniformity requirements of high-repetition-rate solid-state lasers and large-mode-field optical fibers at high doping concentrations, providing a reliable guarantee for achieving excellent optical gain performance.

[0044] Figure 3 This is the EPMA line scan of the Er-Yb co-doped high-P quartz glass in Example 2. As can be seen from the figure, the Si, P, Er, and Yb elements are evenly distributed, the concentration gradient is stable, and there is no obvious fluctuation or segregation phenomenon, which proves the high uniformity of doping. At the same time, the concentration distribution of the P element is uniform, without excessive segregation, and high-concentration doping is successfully achieved. These characteristics fully meet the requirements of high repetition rate solid-state lasers and large mode field optical fibers for high doping uniformity of Er-Yb co-doped high-P quartz core glass.

[0045] Embodiment 3: The components of the Er-Yb co-doped high P quartz glass of this embodiment are: 0.05mol% Er2O3, 0.7mol% Yb2O3, 1mol% Al2O3, 15mol% P2O5, 83.25mol% SiO2, and its preparation method comprises the following steps: S1. Weigh the precursor raw materials of each component according to the selected molar percentage, the precursor raw material of Er2O3 is erbium chloride hexahydrate, the precursor raw material of Yb2O3 is ytterbium chloride hexahydrate, the precursor raw material of Al2O3 is aluminum chloride hexahydrate, the precursor raw material of P2O5 is phosphoric acid, 90wt% of the precursor raw material of SiO2 is porous silica powder, and 10wt% of the precursor raw material of SiO2 is derived from silicon alkoxide; S2. Prepare a mixed solution in a volume ratio of silicon alkoxide: water: organic solvent = 1:6:12, wherein silicon alkoxide is Si(OC2H5)4 and organic solvent is C2H5OH. Add erbium chloride hexahydrate, ytterbium chloride hexahydrate, aluminum chloride hexahydrate and phosphoric acid to the mixed solution in sequence and stir well. Then, add silicon alkoxide hydrolysis catalyst HCl, adjust the pH value of the solution to a first pH value of 3, stir well at room temperature for 10 hours, and obtain Er 3+ , Yb 3+ 、Al 3+ , P 5+ The four-doped silicon oxide transparent sol solution was allowed to stand for another 3 days; S3. The porous silica powder was added in batches in a fixed amount of 3 g each time to the vigorously stirred transparent silica sol solution, and stirring was continued for 30 h after the addition to form a suspension; S4. Granulate the suspension by rotary evaporation to obtain a preliminary powder containing a certain amount of water and organic matter. Subsequently, place the preliminary powder in a tube furnace, slowly increase the temperature from 50°C to 1000°C at a rate of 1°C per minute in an oxygen atmosphere, and keep it at 1000°C for 10 hours to remove residual carbon and hydroxyl groups to form Er-Yb co-doped high-P silica powder; S5. ball milling the silica powder using a ball mill to control the particle size to be less than 100 μm; S6. The ball-milled silica powder was placed in a graphite crucible and heated in a high temperature furnace at 1730°C for 10 -3 The glass is melted for 4 hours under a vacuum degree of 0.1 torr and cooled in the furnace to form bubble-free transparent glass, which is Er-Yb co-doped high-P quartz glass.

[0046] The bubble-free transparent glass was cold processed and polished into 2 mm thick Er-Yb co-doped high-P quartz sheet glass for optical and spectral performance testing and evaluation.

[0047] Figure 4 : is the transmittance curve of Er-Yb co-doped high P quartz glass in the ultraviolet-visible band in Example 3. It can be seen from the figure that Er-Yb co-doped high P quartz glass has a high and stable transmittance in the ultraviolet to visible band. The main advantage of high transmittance is that it can significantly reduce light loss, ensure that more laser energy is effectively transmitted to the target area, thereby improving the working efficiency of the laser and optical fiber.

[0048] Figure 5 The figure is a schematic diagram of the absorption spectrum (Ex = 980nm) of Er-Yb co-doped high P quartz glass at room temperature in Example 3. It can be seen from the figure that Er-Yb co-doped high P quartz glass has a high efficiency in pump light absorption in the 980nm band. This is a key factor in improving the pump conversion efficiency, which can ensure that more light energy is absorbed and effectively used to excite Er ions.

[0049] Figure 6 The figure is a schematic diagram of the emission spectrum (Ex = 980nm) of Er-Yb co-doped high-P quartz glass at room temperature in Example 3. As can be seen from the figure, high phosphorus doping can optimize the energy transfer process between Yb ions and Er ions and enhance the sensitization effect of Yb ions on Er ions. This effect increases the emission intensity of Er ions in the 1.5μm wavelength range, which is beneficial to enhance laser gain and fluorescence emission efficiency.

[0050] Embodiment 4: The components of the Er-Yb co-doped high P quartz glass of this embodiment are: 0.01mol% Er2O3, 0.05mol% Yb2O3, 5mol% P2O5, 94.94mol% SiO2, and its preparation method comprises the following steps: S1. Weighing the precursor raw materials of each component according to the selected molar percentage, the precursor raw material of Er2O3 is erbium chloride hexahydrate, the precursor raw material of Yb2O3 is ytterbium chloride hexahydrate, the precursor raw material of P2O5 is phosphoric acid, 95wt% of the precursor raw material of SiO2 is porous silica powder, and 5wt% of the precursor raw material of SiO2 is derived from silicon alkoxide; S2. Prepare a mixed solution in a volume ratio of silicon alkoxide: water: organic solvent = 1:10:20, wherein silicon alkoxide is Si(OCH3)4 and organic solvent is CH3OH. Add erbium chloride hexahydrate, ytterbium chloride hexahydrate and phosphoric acid to the mixed solution in sequence and stir well. Then, add ammonia water as a silicon alkoxide hydrolysis catalyst and adjust the pH value of the solution to a first pH value of 8. Stir well at room temperature for 10 hours to obtain Er 3+ , Yb 3+ , P 5+ The three-doped silicon oxide transparent sol solution was left to stand for another 3 days; S3. The porous silica powder was added in batches in a fixed amount of 3 g each time to the vigorously stirred transparent silica sol solution, and stirring was continued for 30 h after the addition to form a suspension; S4. Granulate the suspension by rotary evaporation to obtain a preliminary powder containing a certain amount of water and organic matter. Subsequently, place the preliminary powder in a tube furnace, slowly increase the temperature from 50°C to 1000°C at a rate of 1°C per minute in an oxygen atmosphere, and keep it at 1000°C for 10 hours to remove residual carbon and hydroxyl groups to form Er-Yb co-doped high-P silica powder; S5. ball milling the silica powder using a ball mill to control the particle size to be less than 100 μm; S6. The ball-milled silica powder was placed in a graphite crucible and heated in a high-temperature furnace at 1600°C for 10 -3 The glass is melted for 6 hours under a vacuum degree of 0.1 torr and cooled in the furnace to form bubble-free transparent glass, which is Er-Yb co-doped high-P quartz glass.

[0051] Embodiment 5: The components of the Er-Yb co-doped high P quartz glass of this embodiment are: 0.2 mol% Er2O3, 1 mol% Yb2O3, 3 mol% Al2O3, 15 mol% P2O5, 80.8 mol% SiO2, and the preparation method thereof comprises the following steps: S1. Weigh the precursor raw materials of each component according to the selected molar percentage, the precursor raw material of Er2O3 is erbium chloride hexahydrate, the precursor raw material of Yb2O3 is ytterbium chloride hexahydrate, the precursor raw material of Al2O3 is aluminum chloride hexahydrate, the precursor raw material of P2O5 is phosphoric acid, 95wt% of the precursor raw material of SiO2 is porous silica powder, and 5wt% of the precursor raw material of SiO2 is derived from silicon alkoxide; S2. Prepare a mixed solution in a volume ratio of silicon alkoxide: water: organic solvent = 1:10:20, wherein silicon alkoxide is Si(OCH3)4 and organic solvent is CH3OH. Erbium chloride hexahydrate, ytterbium chloride hexahydrate, aluminum chloride hexahydrate and phosphoric acid are added to the mixed solution in sequence and stirred thoroughly. Subsequently, HCl is added as a silicon alkoxide hydrolysis catalyst to adjust the pH value of the solution to a first pH value of 3. After stirring thoroughly at room temperature for 10 hours, Er is obtained. 3+ , Yb 3+ 、Al 3+ , P 5+ The four-doped silicon oxide transparent sol solution was allowed to stand for another 3 days; S3. The porous silica powder was added in batches in a fixed amount of 3 g each time to the vigorously stirred transparent silica sol solution, and stirring was continued for 30 h after the addition to form a suspension; S4. Granulate the suspension by rotary evaporation to obtain a preliminary powder containing a certain amount of water and organic matter. Subsequently, place the preliminary powder in a tube furnace, slowly increase the temperature from 50°C to 1000°C at a rate of 1°C per minute in an oxygen atmosphere, and keep it at 1000°C for 10 hours to remove residual carbon and hydroxyl groups to form Er-Yb co-doped high-P silica powder; S5. ball milling the silica powder using a ball mill to control the particle size to be less than 100 μm; S6. The ball-milled silica powder was placed in a graphite crucible and heated in a high temperature furnace at 1730°C for 10 -3 The glass is melted for 4 hours under a vacuum degree of 0.1 torr and cooled in the furnace to form bubble-free transparent glass, which is Er-Yb co-doped high-P quartz glass.

[0052] Embodiment 6: The components of the Er-Yb co-doped high-P quartz glass of this embodiment are: 0.1 mol% Er2O3, 0.5 mol% Yb2O3, 1.5 mol% Al2O3, 10 mol% P2O5, 87.9 mol% SiO2, and its preparation method comprises the following steps: S1. Weigh the precursor raw materials of each component according to the selected molar percentage, the precursor raw material of Er2O3 is erbium chloride hexahydrate, the precursor raw material of Yb2O3 is ytterbium chloride hexahydrate, the precursor raw material of Al2O3 is aluminum chloride hexahydrate, the precursor raw material of P2O5 is phosphoric acid, 95wt% of the precursor raw material of SiO2 is porous silica powder, and 5wt% of the precursor raw material of SiO2 is derived from silicon alkoxide; S2. Prepare a mixed solution in a volume ratio of silicon alkoxide: water: organic solvent = 1:2:4, wherein silicon alkoxide is Si(OCH3)4 and organic solvent is CH3OH. Erbium chloride hexahydrate, ytterbium chloride hexahydrate, aluminum chloride hexahydrate and phosphoric acid are added to the mixed solution in sequence and stirred thoroughly. Subsequently, ammonia water as a silicon alkoxide hydrolysis catalyst is added to adjust the pH value of the solution to a first pH value of 8, and after stirring thoroughly at room temperature for 10 hours, Er is obtained. 3+ , Yb 3+ 、Al 3+ , P 5+ The four-doped silicon oxide transparent sol solution was allowed to stand for another 3 days; S3. The porous silica powder was added in batches in a fixed amount of 3 g each time to the vigorously stirred transparent silica sol solution, and stirring was continued for 30 h after the addition to form a suspension; S4. Granulate the suspension by rotary evaporation to obtain a preliminary powder containing a certain amount of water and organic matter. Subsequently, place the preliminary powder in a tube furnace, slowly increase the temperature from 50°C to 1000°C at a rate of 1°C per minute in an oxygen atmosphere, and keep it at 1000°C for 10 hours to remove residual carbon and hydroxyl groups to form Er-Yb co-doped high-P silica powder; S5. ball milling the silica powder to control the particle size to be below 100 μm; S6. The ball-milled silica powder was placed in a graphite crucible and heated in a high temperature furnace at 1730°C for 10 -3 The glass is melted for 4 hours under a vacuum degree of 0.1 torr and cooled in the furnace to form bubble-free transparent glass, which is Er-Yb co-doped high-P quartz glass.

[0053] The Er-Yb co-doped high-P quartz glass in Examples 4 to 6 was cold worked and polished into Er-Yb co-doped high-P quartz sheet glass with a thickness of 2 mm for optical and spectral performance testing and evaluation.

[0054] The sheet glasses of Examples 4 to 6 were tested in the same manner as in Example 2 and Example 3, and substantially the same test results as in Example 2 and Example 3 were obtained, which will not be described in detail here.

[0055] The Er-Yb co-doped high-P quartz glass in Examples 4 to 6 was cold processed and polished to obtain an optical fiber core rod, the surface roughness of the optical fiber core rod was less than 10 nm, and the optical fiber core rod was placed in hydrofluoric acid with a mass concentration of 15% for acid treatment for 10 minutes, and then taken out and dried to obtain an Er-Yb co-doped high-P quartz optical fiber core rod. The obtained core rod has a diameter greater than 3 mm and a length greater than or equal to 100 mm.

[0056] The Er-Yb co-doped high-P quartz glass and the preparation method thereof of the present invention realize high doping of P element and accurately control the distribution of P element, solve the problems of Er-Yb co-doped quartz glass such as difficulty in high doping of P2O5, easy phase separation and crystallization, and easy clustering of high-concentration Er ions, overcome the problems of uneven doping and unstable temperature control in the traditional MCVD process, and can prepare Er-Yb co-doped high-P quartz glass with large size, high doping concentration, high doping uniformity and low loss, which is widely applicable to high-repetition-rate solid-state laser gain materials and Er-Yb co-doped large-mode-field optical fiber core rods. At the same time, the method can significantly improve the pump conversion efficiency of Er-Yb co-doped optical fiber, and effectively reduce the nonlinear effect in the optical fiber, thereby improving the stability and long-term reliability of the laser system when working at high power.

[0057] The present invention has been described by the above-mentioned relevant embodiments, but the above-mentioned embodiments are only examples for implementing the present invention. In addition, the technical features involved in the different embodiments of the present invention described above can be combined with each other as long as they do not conflict with each other. It must be pointed out that the disclosed embodiments do not limit the scope of the present invention. On the contrary, changes and modifications made without departing from the spirit and scope of the present invention are all within the scope of patent protection of the present invention.

Claims

1. An Er-Yb co-doped high P quartz glass, characterized in that: The molar percentages of the components of the Er-Yb co-doped high-P quartz glass are: Er2O3: 0.01mol% to 0.2mol%, Yb2O3: 0.05 to 1mol%, Al2O3: 0 to 3mol%, P2O5: 5mol% to 15mol%, and the remaining components are SiO2.

2. A method for preparing Er-Yb co-doped high-P quartz glass, characterized in that: The following steps are involved: S1. Weigh the precursor raw materials of each component according to the selected molar percentage, the precursor raw material of Er2O3 is erbium chloride hexahydrate, the precursor raw material of Yb2O3 is ytterbium chloride hexahydrate, the precursor raw material of Al2O3 is aluminum chloride hexahydrate, the precursor raw material of P2O5 is phosphoric acid, 90wt% to 95wt% of the precursor raw material of SiO2 is porous silica powder, and 5wt% to 10wt% of the precursor raw material of SiO2 is derived from silicon alkoxide; S2. A mixed solution is prepared according to a volume ratio of silicon alkoxide: water: organic solvent = 1:2~10:4~20, and then erbium chloride hexahydrate, ytterbium chloride hexahydrate, aluminum chloride hexahydrate, and phosphoric acid are sequentially added to the mixed solution, and then a silicon alkoxide hydrolysis catalyst is added to adjust the pH value of the solution to a first pH value, and the mixture is stirred for 1 to 20 hours at room temperature to obtain Er 3+ , Yb 3+ , P 5+ Triple doped or Er 3+ , Yb 3+ 、Al 3+ , P 5+ The silicon oxide transparent sol solution is added and allowed to stand for 1 to 5 days; S3. The porous silica powder is added in batches in a fixed amount to the vigorously stirred transparent silica sol solution, and stirring is continued for 2 to 48 hours after the addition is completed to form a suspension; S4. The suspension is granulated to obtain a preliminary powder, and then the preliminary powder is heated to 1000°C in an oxygen atmosphere in a tube furnace and kept at 1000°C for 5 to 20 hours to remove residual carbon and hydroxyl groups to form an Er-Yb co-doped high P silica powder; S5. The silica powder is ball-milled using a ball mill and the particle size is controlled to be below 100 μm; S6. The ball-milled silica powder is placed in a graphite crucible and placed in a high temperature furnace at 1500 to 1730°C for 10 -1 Up to 10 - 3 The melting is carried out for 1 to 8 hours under a vacuum degree of torr, and bubble-free transparent glass is formed along with furnace cooling. The bubble-free transparent glass is Er-Yb co-doped high-P quartz glass.

3. The method for preparing Er-Yb co-doped high P quartz glass according to claim 2, characterized in that: The molar percentages of the components of the Er-Yb co-doped high-P quartz glass are: Er2O3: 0.01mol% to 0.2mol%, Yb2O3: 0.05 to 1mol%, Al2O3: 0 to 3mol%, P2O5: 5mol% to 15mol%, and the remaining components are SiO2.

4. The method for preparing Er-Yb co-doped high-P quartz glass according to claim 2, characterized in that: The silicon alkoxide is Si(OC2H5)4 or Si(OCH3)4. When the silicon alkoxide is Si(OC2H5)4, the organic solvent is C2H5OH; when the silicon alkoxide is Si(OCH3)4, the organic solvent is CH3OH.

5. The method for preparing Er-Yb co-doped high P quartz glass according to claim 2, characterized in that: The silicon alkoxide hydrolysis catalyst is hydrochloric acid or ammonia water. When the silicon alkoxide hydrolysis catalyst is hydrochloric acid, the first pH value is 1 to 3; when the silicon alkoxide hydrolysis catalyst is ammonia water, the first pH value is 8 to 10.

6. The method for preparing Er-Yb co-doped high P quartz glass according to claim 2, characterized in that: The median particle size of the porous silica powder is in the micro-nano order.

7. The method for preparing Er-Yb co-doped high P quartz glass according to claim 2, characterized in that: In step S3, the fixed addition amount is 1 to 5 g each time.

8. The method for preparing Er-Yb co-doped high P quartz glass according to claim 2, characterized in that: In step S4, the suspension is granulated by rotary evaporation.

9. A method for preparing an Er-Yb co-doped high-P quartz optical fiber core rod, characterized in that: The following steps are involved: The Er-Yb co-doped high-P quartz glass prepared by the preparation method of Er-Yb co-doped high-P quartz glass according to any one of claims 2 to 8 is subjected to cold working and polishing to obtain an optical fiber core rod, wherein the surface roughness of the optical fiber core rod is less than 10 nm, and the optical fiber core rod is placed in hydrofluoric acid with a mass concentration of 5 to 20% for acid treatment for 5 to 15 minutes, and then taken out and dried to obtain an Er-Yb co-doped high-P quartz optical fiber core rod.

10. An Er-Yb co-doped high P silica optical fiber core rod, characterized in that: The Er-Yb co-doped high-P quartz optical fiber core rod is obtained by the preparation method of the Er-Yb co-doped high-P quartz optical fiber core rod according to claim 9.

Citation Information

Patent Citations

  • Rare earth, lanthanum and aluminum codoped quartz glass and preparation method thereof

    CN105481246A

  • Radiation-resistant silica optical fiber preform mandrel and preparation method thereof

    CN112094052A

  • Ytterbium-doped active optical fiber for high-power large mode field and preparation method thereof

    CN112596148A

  • Large-mode-field single-mode radiation-resistant erbium-ytterbium co-doped optical fiber and preparation method thereof

    CN113917599A

  • Three-cladding erbium-ytterbium co-doped optical fiber and preparation method and application thereof

    CN114721087A